The preliminary results on the push factors for the elderly to move to retirement villages in Malaysia - Farah Ajlaa Julaihi; Asmah Alia Mohamad Bohari; Mohd Azrai Azman; Kuryati Kipli; Sharifah Rahama Amirul (Penerbit UPM, 2022)
Many countries are witnessing a rise in the ageing population, which has become a global phenomenon that all nations must address. As the population of greying people is expected to increase in Malaysia, the demand for senior citizen accommodation is predicted to have experienced a major rise by 2030. However, although studies related to retirement villages (RV) are highly important to understand how to provide a better ambience for the elderly, research on the development of retirement villages in Malaysia is yet to gather pace fully. Thus, this paper aims to explore the potential of the retirement village in Malaysia by focusing on the push factors for the elderly to move to retirement villages in the local Malaysian context. The outcome of this paper presents the initial findings derived from a literature review and pilot survey. Eight potential push factors were identified after questions were posed to potential respondents through a pilot survey questionnaire. The research revealed that the main potential reason why the elderly relocate to retirement villages was related to social factors, with the elderly preferring better access to healthcare and support due to their unique requirements. The findings of this study are relevant to Chapter 11, as underlined in the Sustainable Development Goals (SDGs), which call on all governments to offer access to a secure, green environment for everyone, especially the elderly. Theoretically, this research provides the first findings on the elements that encourage the elderly to relocate to an RV when they retire in Malaysia.